Greek family-business management performance: Emotionally intelligent or Machiavellian? - Tsirimokou, Chrysoula; Richardson, Clive; Palaskas, Theodosios (International Conference on Business and Economics - Hellenic Open University, 2023)
Abstract Although the investigation of emotional intelligence levels and personality traits such as Machiavellian behavior of the manager and the family firm’s workforce is critical in understanding the role of emotions in family business dynamics and in drawing conclusions regarding their effects on the overall business performance, the subject has not been examined adequately. Utilizing modern tools, this paper aims to measure and evaluate the qualitative characteristics of family business managers’ behavior to analyze their influence on the firms’ performance. In particular, it examines whether emotional intelligence and Machiavellianism determine the efficiency of the management in Greek family businesses’ performance. For this purpose, a structural equation model was specified and applied to fieldwork data to test the statistical validity of the hypothesis. The findings suggest that, while emotional intelligence plays an important role, Machiavellian personality does not. EL Classifications: Key words: emotional intelligence, Machiavellianism, family business, management, structural equation models